Effect of single and double austenitization treatments on the microstructure and mechanical properties of 16Cr-2Ni steel - Balan K.P.; Venugopal Reddy A.; Sarma D.S. (My University, 2025)
Double austenitization (DA) treatment is found to yield the best combination of strength and toughness in both low-temperature as well as high-temperature tempered conditions as compared to single austenitization (SA) treatments. Obtaining the advantages of double austenitization (DA) to permit dissolution of alloy carbides without significant grain coarsening was attempted in AISI 431 type martensitic stainless steel. Structure-property correlation after low-temperature tempering (200 °C) as well as high-temperature double tempering (650+600 °C) was carried out for three austenitization treatments through SA at 1000 °C, SA at 1070 °C, and DA at 1070+1000 °C. While the increase in strength after DA treatment and low-temperature tempering at 200 °C is due to the increased amount of carbon in solution as a result of dissolution of alloy carbides during first austenitization, the increased toughness is attributable to the increased quantity of retained austenite. After double tempering (650+600 °C), strength and toughness are mainly found to depend on the precipitation and distribution of carbides in the microstructure and the grain size effect.